How Do Video Games Elicit Guilt in Players? Linking Character Morality to Guilt Through a Mediation Analysis - Ahn, Changhyun; Grizzard, Matthew; Lee, Seyoung (Frontiers in Psychology, 2021)
Research has consistently found that committing immoral actions in video games is capable of eliciting feelings of guilt in players. This study aimed to investigate the mediating role of theoretically-relevant psychological mechanisms: Perceived morality of the player-controlled character and self-attribution of virtual behavior. Based in psychological and communication theory, we derived a mediation model that links these mediating variables to character biography and guilt: Controlling an immoral character should decrease perceived morality of character, which reduce self-attribution of virtual behavior, which in turn, predict guilt. A between-subjects experiment manipulated the biography of the player-controlled character (immoral versus moral) and measured the mediating variables and self-reported guilt. The hypothesized model was tested using PROCESS macro on SPSS. Data were generally consistent with hypotheses. Perceived morality of character and self-attribution of virtual behavior mediated the impact of character biography on guilt. Implications of the findings, contributions of our method, and directions for future research are discussed.